Hydrochemical study and Water quality of Tigris Channel at Al- Taji area, Northern Baghdad - Abbood, Ayat K.; Abdullah, Enaam J; Al-Paruany, Kamal B (Iraqi Journal of Science, 2024)
The water quality of the Tigris Channel at Al-Taji area were studied in both periods (August, and March, 2022). Eight samples were collected from Tigris channels to investigate water quality and parameters such as electrical conductivity (EC), total dissolved solids (TDS), Temperature (T), hydrogen number (pH), Total Hardness (T.H), as well as significant cations (Ca2+, Mg 2+, Na+, and K+), significant anions (CO32-, HCO3 -, Cl- and SO42-) and Heavy metals (Cd, Pb, Fe, Zn, Ni and Cr). The results show that the maximum value of EC is 1182 (µS/cm) in Ch3 in the dry period, while the lowest value of EC is1105 (µS/cm) in Ch1 in the wet period. The hydrochemical formula of water samples in both periods is CaCl. In this study, the dominating cation is Ca2+, followed by Na+, Mg2+, and K+, whereas the dominant anion is Cl-, followed by SO42-, HCO3-, and CO3-. According to Piper’s illustration, all water samples that fall in class (e) are arranged together for both periods (wet and dry) "Earth alkaline water with a higher percentage of alkali and a sulfate and chloride predominance." Finally, the WQI is rated excellent for the wet Tigris channel and good water for the dry Tigris channel.